2016
DOI: 10.1103/physrevapplied.6.054010
|View full text |Cite
|
Sign up to set email alerts
|

Purcell-Enhanced Single-Photon Emission from Nitrogen-Vacancy Centers Coupled to a Tunable Microcavity

Abstract: Optical microcavities are a powerful tool to enhance spontaneous emission of individual quantum emitters. However, the broad emission spectra encountered in the solid state at room temperature limit the influence of a cavity, and call for ultra-small mode volume. We demonstrate Purcellenhanced single photon emission from nitrogen-vacancy (NV) centers in nanodiamonds coupled to a tunable fiber-based microcavity with a mode volume down to 1.0 λ 3 . We record cavity-enhanced fluorescence images and study several … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
83
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 99 publications
(83 citation statements)
references
References 55 publications
(64 reference statements)
0
83
0
Order By: Relevance
“…[13][14][15][16] In recent years, the open Fabry-Perot microcavity 17 has emerged as a promising platform for diamond emitters. [18][19][20][21][22] Such a microcavity provides in-situ spatial and spectral tunability, while reaching strong field confinement due to its small mode volume V and high quality factor Q. Moreover, this architecture allows for the use of diamond slabs 23 in which the NV center can be relatively far removed from surfaces and thus exhibit bulklike optical properties, as required for quantum network applications.…”
mentioning
confidence: 99%
“…[13][14][15][16] In recent years, the open Fabry-Perot microcavity 17 has emerged as a promising platform for diamond emitters. [18][19][20][21][22] Such a microcavity provides in-situ spatial and spectral tunability, while reaching strong field confinement due to its small mode volume V and high quality factor Q. Moreover, this architecture allows for the use of diamond slabs 23 in which the NV center can be relatively far removed from surfaces and thus exhibit bulklike optical properties, as required for quantum network applications.…”
mentioning
confidence: 99%
“…The authors also carried out systematic studies using concave mirrors with a series of RoCs ranging from 4 to 25 µm, and concluded that RoC = 8 µm enabled the best device performance by the interplay between cavity feeding and photon extraction. With fiber‐based cavities, Kaupp et al., demonstrated Purcell enhancement up to two of NV centers in nanodiamonds in 2016 . In 2017, Riedel et al.…”
Section: Single‐photon Emitters and Nanoparticles In Open‐access Micrmentioning
confidence: 99%
“…This modification was historically treated by Purcell using a semi-classical approach, with the essential results subsequently confirmed by rigorous quantum mechanical treatments [23]. For example, assuming an atom located at a field maximum (in an otherwise empty cavity, such that refractive index n =1) and with its electric dipole aligned to the cavity mode field, and also assuming the atomic transition is exactly matched to a cavity resonance and with γ < κ [53,71], then the enhancement of the radiative decay rate is given by the so-called Purcell factor:…”
Section: Cqed -Overviewmentioning
confidence: 99%
“…In the case of solid-state emitters, which have relatively large g, this implies that small VM is particularly critical (i.e. since increased k implies reduced Q) [53,71]. …”
Section: Cqed -Overviewmentioning
confidence: 99%